2015
DOI: 10.4103/2008-7802.151827
|View full text |Cite
|
Sign up to set email alerts
|

The attitude of physicians toward the use of patient decision aids in iran as a developing country

Abstract: Background:The patient decision aids (PDAs), which can facilitate the decision-making process when choosing the optimal method of treatment, are a challenge to patients. This study tried to determine the attitude of physicians on the barriers of using PDAs in the way of prioritizing and proposing solutions to them.Methods:This study was a cross-sectional research carried out on 150 clinical faculty members of research centers and scientific associations affiliated with Tehran University of Medical Sciences. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Physician knowledge and adherence to guidelines pose additional challenges. A Study in Iran reported that only 31.8% of physicians were familiar with clinical guidelines 40 , and family physicians adhered to only one-third of the recommendations in the national hypertension guideline 19 . Among cardiologists at a teaching hospital in Iran, only 60% exhibited high adherence to the ACC/AHA guidelines in managing cardiovascular disease risk factors 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Physician knowledge and adherence to guidelines pose additional challenges. A Study in Iran reported that only 31.8% of physicians were familiar with clinical guidelines 40 , and family physicians adhered to only one-third of the recommendations in the national hypertension guideline 19 . Among cardiologists at a teaching hospital in Iran, only 60% exhibited high adherence to the ACC/AHA guidelines in managing cardiovascular disease risk factors 41 .…”
Section: Discussionmentioning
confidence: 99%
“…7 In spite of the proven benefits of decision aids, they are rarely used in Iran since some physicians believe that the use of decision aids could lead to patients perceiving the physician as less reliable (or decisive), or to less patient satisfaction. 8 While, studies have shown a positive attitude toward the use of decision aids among Iranian patients. [8][9][10] SDM tools have been demonstrated to increase patients' knowledge, reduce decisional conflict, and reduce the proportion of patients who are passive in the decision making process or remain undecided.…”
mentioning
confidence: 99%
“…8 While, studies have shown a positive attitude toward the use of decision aids among Iranian patients. [8][9][10] SDM tools have been demonstrated to increase patients' knowledge, reduce decisional conflict, and reduce the proportion of patients who are passive in the decision making process or remain undecided. 11 The implication is that for Iran, realistically, SDM tools need to be developed, tested, and implemented that are consistent with the culture of Iranian patients and clinicians.…”
mentioning
confidence: 99%